THE ENFORCEMENT OF CYBERCRIME LAW WITHIN THE LEGAL SYSTEM OF INDONESIA - Rafie, Patih Ahmad; Merta, M. Martindo; Junaidi, Junaidi (Transpublika Publisher, 2024)
This study aims to analyze the legal regulations on cyber crime in the Indonesian legal system. The research method used is document analysis, by examining Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE Law) and other related literature. The analysis results show that the legal regulations on cyber crime in Indonesia are governed by the ITE Law, which regulates various criminal actions related to the use of information and communication technology. In addition to the ITE Law, there are also other regulations that govern cyber crimes. However, there is a need for the enactment of the Cyberlaw Bill to provide a more specific and comprehensive legal basis for addressing cyber crimes. With specific laws regulating cyber crimes, law enforcement can be carried out more effectively and efficiently, providing legal certainty for cyber crime victims, and offering better legal protection for them. Therefore, this study concludes that legal regulations on cyber crimes need to be continuously developed and updated in accordance with the development of technology and the evolving trends of cyber crimes.